The Basic Theory and Implementation of Mahārah Al- Istimā’ in Higher Education - Sholehuddin, M. Sugeng; Ahmad Taufiq; Setyawan, Cahya Edi; Fathoni, Muhamad (ALSINATUNA, 2020)
Listening skill is one of the important points in language teaching. In teaching Arabic (listening), it becomes the first element of competence. Listening is receptive efficiency, so it is important in college. Every student must have an unconscious understanding of this proficiency. The purpose of this research is to study the basic theory and the implementation of mahārah al- istimā’ in higher education. The research method is to search the references using a qualitative approach. Interviews and library research were conducted to collect the data which then concluded for a new thesis. Language acquisition is based on the theories of listening in Qur'anic verses, language acquisition devices, perception, motivational response, and the linguistic environment. The main thing is that listening is a part of a language acquisition. The listening skill theory has evolved from linguistics theory to the theory of receptive language teaching, which is the overall psychological response, the natural approach, and the silent period. The stages of the listening skill in higher education use an Arabic standard based on ACTFL and MSA, which is then applied in the unit book. The sample of the higher education unit books are TOSA and ALBA.